Reduced spontaneous low frequency oscillations as measured with functional near-infrared spectroscopy in mild cognitive impairment. - Zeller, Julia B. M.; Katzorke, Andrea; Müller, Laura D.; Breunig, Judith; Haeussinger, Florian B.; Deckert, Jürgen; Warrings, Bodo; Lauer, Martin; Polak, Thomas; Herrmann, Martin J. (Brain Imaging & Behavior, 2019)
Spontaneous low frequency oscillations (LFO) in functional imaging data have gained increased interest in the study of cognitive decline. Persons diagnosed with mild cognitive impairment (MCI) and Alzheimer's disease (AD) display alterations in their amount of LFO in various brain regions. This is commonly interpreted as disruptions in the autoregulation of the cerebral microvascular system. In the present study LFO (0,07-0,11 Hz) were measured with 52-channel near-infrared spectroscopy (NIRS) in 61 healthy elderly persons (70-76 years), 54 MCI subjects (70-76 years) and 25 healthy young controls (21-48 years) during rest over the frontal and the parietal cortex. Both MCI and healthy elderly controls showed less LFO in the frontal cortex as compared to young subjects. For the parietal cortex a decrease in LFO could be observed for the MCI group in comparison to healthy elderly subjects. Correlations of more LFO with worse performance in neuropsychological tests point to compensatory processes. LFO measured with NIRS might be especially suited for longitudinal studies aiming at predicting cognitive decline.